Individualized approach to elexacaftor/tezacaftor/ivacaftor dosing in cystic fibrosis, in response to self-reported anxiety and neurocognitive adverse events: A case series - Ibrahim, Hisham; Danish, Hammad; Morrissey, David; Deasy, Kevin F.; McCarthy, Mairead; Dorgan, James; Fleming, Claire; Howlett, Ciara; Twohig, Sarah; Vagg, Tamara; Murphy, Desmond M.; Maher, Michael; et al. (Frontiers in Pharmacology, 2023)
The prevalence of mental health disorders is high among people with Cystic Fibrosis (CF). The psychological symptoms in CF are associated with poor adherence, worse treatment outcomes, and greater health utilization/cost. Mental health and neurocognitive adverse events have been reported with all available Cystic Fibrosis Transducer Regulator (CFTR) modulators in small groups of patients. We report our experience with a dose reduction strategy in 10 of our patients on elexacaftor/tezacaftor/ivacaftor (7.9% of total number of patients) who self-reported developing anxiety, irritability and/or mental slowness after initiation of full dose treatment. Standard dose elexacaftor/tezacaftor/ivacaftor resulted in 14.3 points improvement in mean Percent Predicted Forced Expiratory Volume in 1 second (ppFEV1), and a mean difference in sweat chloride of -39.3mmol/L. We initially discontinued and/or reduced therapy according to symptom severity, with a subsequent planned dose escalation every 4-6 weeks guided by sustainability of clinical effectiveness, absence of symptom recurrence, and patients’ preferences. Clinical parameters including lung function and sweat chloride were monitored for up to 12 weeks to assess ongoing clinical response to the reduced dose regimen. Dose reduction resulted in resolution of self-reported mental/psychological side effects, without loss of clinical effectiveness (ppFEV1 was 80.7% on standard dose, and 83.4% at 12 weeks on reduced dose; sweat chloride was 33.4 mmol/L and 34 mmol/L on standard and reduced dose, respectively). Furthermore, in a subgroup of patients who completed 24 weeks of the reduced dose regimen, repeat low dose Computed Tomography (CT) imaging showed a significant response when compared to pre-initiation of elexacaftor/tezacaftor/ivacaftor.